ANALISIS PEMIKIRAN FILSAFAT PENDIDIKAN AKHLAK IBNU MISKAWAIH DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM KONTEMPORER - Rizqi Lestari; Fatimah Zahroh Napitupulu; Viva Fadma Onilivia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the analysis of philosophical figures, namely the thought of ibnu miskawaih from biography, the concept of akhaq education thought, and its relevance in contemporary, Education is an important part of human life that can never be abandoned, education is an effort made by someone in order to change towards the better. Ibn Miskawaih is one of the Islamic philosophical figures who contributed thoughts to education. This study uses a qualitative approach with library research with data sources based on literature studies. The results showed that the concept of moral education Ibn Miskawaih argues that the basic concept of akhlaq education is based on the doctrine of al-wasath or the middle way balanced between two extremes and harmony. However, he is more inclined to the definition of balance between extremes of deficiency and extremes of excess is the virtue of morals. the concept of education is very relevant to this education system which includes physical education, mental education and skills education in a unified whole, with moral ties